2016
DOI: 10.1515/jpem-2015-0290
|View full text |Cite
|
Sign up to set email alerts
|

Urate crystals deposition in the feet of overweight juveniles and those with symptomatic hyperuricemia: a dual-energy CT study

Abstract: Urate crystals deposition can be detected by dual-energy CT in the feet of symptomatic hyperuricemia juveniles. DECT can be a valuable diagnostic tool for helping diagnose in juvenile gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Meanwhile our previous research found that MSU crystal deposition can be observed in hyperuricemic children [5]. It suggests that some patients with HUA have developed joint disease, and it may significantly affect their quality of life.…”
Section: Introductionmentioning
confidence: 91%
“…Meanwhile our previous research found that MSU crystal deposition can be observed in hyperuricemic children [5]. It suggests that some patients with HUA have developed joint disease, and it may significantly affect their quality of life.…”
Section: Introductionmentioning
confidence: 91%
“…In addition, a complete blood count with differential and serum uric acid levels should be done every 6 months [ 111 ]. While there are no published data to evaluate the clinical significance of elevated uric acid levels associated with the use of diazoxide, studies in other populations have shown that chronic hyperuricemia in children can lead to monosodium urate deposits that may progress to gout, just as in adults [ 118 ]. Thus, we consider it important to screen for hyperuricemia in children treated with diazoxide given the reported 5% frequency of hyperuricemia in this population [ 109 ].…”
Section: Medical Managementmentioning
confidence: 99%
“…In pediatric patients, chronic hyperuricemia is often associated with underlying comorbidities such as cardiovascular disease or kidney disease, inborn errors of purine metabolism, genetic disorders, or kidney transplantation [2][3][4][5][6][7][8][9][10][11][12][13]. Gout is relatively rare in the pediatric population, but diagnostic studies with dual energy computed tomography technology have shown that chronic sustained hyperuricemia in children can lead to monosodium urate deposits that may progress to gout, just as in adults [14][15][16]. Recent trends have shown that child obesity is increasing, which suggests a possible correlation to the prevalence of gout and hyperuricemia in pediatric patients and which parallels the increasing incidence of gouty arthritis at younger ages [17][18][19].…”
Section: Introductionmentioning
confidence: 99%